(untitled) (Aporte Santiaguino, 2025)
In areas near to the equator, there are serious difficulties for the location and inclination of thermal and photovoltaic installations, due to the presence of cloud cover, heavy rainfall, variable microclimates and change in the daily angular position of the sun, that form apparent trajectories, which considering the solar noon and the vertical of the locality, form zenith angles that change from +23.45° on June 21 to -23.45° on December 22 of each year. These factors significantly reduce the capacity to capture sunlight, and consequently the performance of fixed installations that use solar energy for their operation. Also, the lack of knowledge of these climatic conditions and solar radiation can significantly affect the optimal sizing of flat collectors or photovoltaic panels, with the consequent low energy productivity and minimum benefit-cost ratio. Therefore, the objective of this research is to determine the optimal angles of inclination, for which the city of Sangolquí-Ecuador is taken as a reference, which is located at a latitude of -0.3º and a longitude of -78.44º.